Equity And Equality In Education Financing - Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2019)
Education is part of the basic needs of humans in carrying out their vision and mission as human beings on earth which is always universal. All humans without exception on this earth really need education. For this reason, the presence of the government in meeting universal educational needs is highly awaited by all the children of the nation in the Unitary State of the Republic of Indonesia. This paper is presented in the hope of being able to provide an explanation and elaborate on equity equality and the education funding system which includes several discussions; and understanding of equality, equality, strategies and efforts of the Government in maximizing educational equity and the impact of the lack of equitable education in Indonesia, as well as the role of the funding system that is applied to the equal distribution of education.